PERBANDINGAN NARASI NOVEL DAN FILM (Analisis Novel dan Film The Kite Runner karya Khaled Hosseini) - Haryati Sulistyorini; Budi Santoso (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
This paper entitled A Comparison of the Narrative Perspective between Novel and Film is the result of a research which is done by comparing a plot of the story in â€œThe Kite Runnerâ€ novel with the film. The objective of this research is to find out the differences between plot from the text andÂ  the film in the narrative perspective. The method used is library research method. This is a method which is done to find out references by reading the novel, some books or references dealing with the object of analysis. Beside that, the data collection is also done by comparing the sequence of plot in the novel and Â the film.Â Â Â  The result of this research shows that most of the narrative perspective from the novel and the film are the same. The simillarites are especially on the part of narrative structure. They are divided into exposition, compilation, climax and resolution. However, there are some differences on the way how this story resolves the tension. The resolution in the novel is rather different from the one in the film. Besides that the way how this novel present the psychological description of Amir as the main character is also different. The novel presents the psychological of the main character deeply, meanwhile it doesnâ€™t appear in the film. Finally over all, between the novel and the film, they still have many similarities. Key words : film, novel, plot